Protection of fuel filter with alkaline and acid zinc coatings - Šćepanović, Jelena; Herenda, Safija; Korać, Fehim; Vuksanović, Darko; Radonjić, Dragan (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2019)
Galvanic coatings are applied so that the surface of the base material obtains appropriate properties, corrosion resistance, durability, aesthetic appearance, and long-term application in the appropriate industry. In this paper, the aim was to protect steel fuel filters with alkaline and acid zinc coatings of different thicknesses. The coating of zinc, which is applied from the alkaline electrolyte, provides good corrosion protection with excellent coating flexibility. The thickness of the coating by the X-ray fluorescence method was tested, followed by coating tests, corrosion resistance, and electrochemical tests. The results of adhesion showed a high quality coating, as no corrosion occurred during the test. The corrosion resistance tested by the salt chamber method speaks of the appearance of white and red corrosion. On alkaline electrolyte coatings, white corrosion occurred after 168 hours of exposure to the salt test, while on white zinc samples there was a white corrosion after 240 hours of exposure. Tafel polarization diagrams have been determined: corrosion potentials, current intensities, anode and cathode Tafel coefficients and calculated corrosion rates. The active and passive corrosion zone is determined by the cyclic voltammetry.